293 Improving the Quality of Dementia Care in General Practice: A Qualitative Study. (16th September 2019) - Bourque, Meghan; Foley, Tony
Abstract: Background: The prevalence of dementia in Ireland is rising. General Practitioners (GPs) play a central role in caring for people with dementia. There is a growing demand for community-based care, emphasized by the Irish National Dementia Strategy (INDS). The INDS advocates a multidisciplinary, community-based approach to dementia care. However, there is a paucity of research exploring GPs' views on dementia since publication of the INDS. The aim of the study is to develop a deeper understanding of how to improve the quality of dementia care in General Practice from the perspective of Irish GPs. Methods: Semi-structured interviews were conducted with GPs. GPs who completed a continuing professional development module in Cork on dementia in primary care were purposively recruited. Interviews were analyzed thematically. Analysis was iterative and ongoing with data collection. Results: 12 (34.3%) GPs agreed to participate. 10 interviews have been conducted to-date. Participants were evenly distributed by sex (5 male, 5 female). Experience in General Practice varied (3-32 years). Most GPs practiced in mixed urban-rural settings (n=8) and had nursing home commitments (n=7). The average interview length was approximately 45 minutes. Three major themes emerged from the data set: factors promoting care in current practice; resistance to care; and recommendations to improve care. Continuity of care, early disease recognition, coding, audit, and coordinated care teams were recognized as factors promoting quality care. Time, funding, access to secondary care, and inadequate community resources hindered care. GPs emphasized the need for coordinated community services, GP education, review of the chronic disease management scheme for GPs, and service standardization in order to improve care. Conclusion: GPs find dementia care to be a complex, challenging aspect of primary care. While education and training is advocated by GPs, service delivery also needs to be reconfigured. Dementia needs to be included under chronic disease management in Ireland and services must become standardized.